2022
DOI: 10.3390/antiox11040612
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Edged Sword of Oxidative Stress in Skin Damage and Melanoma: From Physiopathology to Therapeutical Approaches

Abstract: The skin is constantly exposed to exogenous and endogenous sources of reactive oxygen species (ROS). An adequate balance between ROS levels and antioxidant defenses is necessary for the optimal cell and tissue functions, especially for the skin, since it must face additional ROS sources that do not affect other tissues, including UV radiation. Melanocytes are more exposed to oxidative stress than other cells, also due to the melanin production process, which itself contributes to generating ROS. There is an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 127 publications
1
49
0
Order By: Relevance
“…Under physiological conditions, there is a balance between the production and elimination of ROS [ 43 ]. Disruption of the redox homeostasis can promote several cancer types, including melanoma, which is in agreement with the literature [ 44 , 45 ]. ROS participate in the pathways related to proliferation, survival, invasion and metastasis [ 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Under physiological conditions, there is a balance between the production and elimination of ROS [ 43 ]. Disruption of the redox homeostasis can promote several cancer types, including melanoma, which is in agreement with the literature [ 44 , 45 ]. ROS participate in the pathways related to proliferation, survival, invasion and metastasis [ 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, ROS at high levels can have negative consequences, such as DNA damage and cell death, conferring an antitumor profile to these molecules. Many studies have reported ROS as a therapeutic strategy in the fight against cancer [ 44 , 50 , 51 , 52 , 53 ]. The treatment of molecules such disulfiram, brusatol and Buthionine sulfoximine render melanoma cells more sensitive to chemo- and radiotherapy through the modulation of redox homeostasis [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduction of antioxidant defenses has been proposed as anticancer, sensitizer therapy in the treatment of melanoma, as recently reviewed [ 25 ]. However, also to be considered is the role played by NRF2-dependent antioxidant responses in limiting the side effect of chemotherapeutic drugs on normal tissues, as demonstrated for other tumors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the ACOX1-induction of ROS production was demonstrated to be involved in oxidative DNA damage and the progression of hepatocellular carcinoma (HCC) [ 50 ]. Ultraviolet (UV) radiation is also an important factor that contributes to ROS generation and subsequent carcinogenesis [ 51 ]. Cells exhibit an increased production of ROS when exposed to UV radiation.…”
Section: Redox Homeostasis: the Biological Basis For Antioxidant Therapymentioning
confidence: 99%